2016
DOI: 10.1016/j.jhevol.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary relationships and age of Homo naledi: An assessment using dated Bayesian phylogenetic methods

Abstract: Homo naledi is a recently discovered species of fossil hominin from South Africa. A considerable amount is already known about H. naledi but some important questions remain unanswered. Here we report a study that addressed two of them: "Where does H. naledi fit in the hominin evolutionary tree?" and "How old is it?" We used a large supermatrix of craniodental characters for both early and late hominin species and Bayesian phylogenetic techniques to carry out three analyses. First, we performed a dated Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
160
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(179 citation statements)
references
References 48 publications
10
160
1
2
Order By: Relevance
“…This general assumption has commonly guided the interpretation of fossil discoveries with poor geological or stratigraphic context, including initial estimates for the age of the H. naledi fossils (Thackeray, 2016; Dembo et al, 2016). The new age estimates for H. naledi show that an approximate age for the hominin fossil fragments cannot be simply deduced from their morphology (Thackeray, 2016; Dembo et al, 2016). Detailed geological investigations are critical before any attempt to ascribe an age to the fossils is made, and even then great care must be taken in interpreting results, which may not always be conclusive (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This general assumption has commonly guided the interpretation of fossil discoveries with poor geological or stratigraphic context, including initial estimates for the age of the H. naledi fossils (Thackeray, 2016; Dembo et al, 2016). The new age estimates for H. naledi show that an approximate age for the hominin fossil fragments cannot be simply deduced from their morphology (Thackeray, 2016; Dembo et al, 2016). Detailed geological investigations are critical before any attempt to ascribe an age to the fossils is made, and even then great care must be taken in interpreting results, which may not always be conclusive (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…U-Th dating is more precise in the <500 ka range than U-Pb dating, and is much less critically affected by detrital material. The initial tests with U-Th disequilibrium dating revealed that the fossils may be much younger than originally anticipated (e.g., Dembo et al, 2016; Thackeray, 2016), and mostly well within the range of the U-Th technique. Therefore, U-Pb dating was not pursued further.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Lower Pleistocene hominins from the Gran Dolina site (Burgos, Spain) are hypothetical ancestors of H. heidelbergensis (and thus Neanderthals) and are also thought to have large thoraces because of their long clavicles 6,30 . Whether H. antecessor is actually a species itself or represents an European branch of H. erectus / ergaster 34 , recent Bayesian analyses 58,59 suggest that H. antecessor belongs to a basal clade of modern human and Neanderthals, alongside other early Homo species such as H. erectus , ergaster and the recently discovered species named as H. naledi 60 . Therefore, H. antecessor could be used as an approach to test whether large bodied early Homo species already presented a large TLC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recently discovered Dinaledi (Homo naledi) sample provides a distinctly human tarsometatarsal skeleton, its lateral pedal proximal phalanges have been described as having a mixture of australopith and later human features (Harcourt-Smith et al, 2015). Unfortunately, secure dates for this sample remain elusive (Dembo et al, 2016). It therefore remains unclear when the full morphology of the human lateral forefoot emerged.…”
Section: Introductionmentioning
confidence: 99%